Social Advertising in Modern Communication Space - Suprun, V.М.; Suprun, L.V. (Science and Innovation, 2024)
Introduction. The evolutionary progress of the modern society is not conceivable without the cultivation of high sociocultural values. Therefore, social advertising becomes an information creator in the field of communication space. Problem Statement. The main problems that need to be solved are elaborating effective mechanisms for the creation and distribution of social advertising and raising the level of its influence on axiological markers of the society. Purpose. To study the implementation forms, functions, and effectiveness of social advertising as public conduct standards represented at the level of mass-communication space. Materials and Methods. Based on the modern information and communicative space of Ukraine, through empiricism of the data, the specificity of social advertising has been analyzed. Results. The main constitutive characteristics, features, and functions of social advertising, as well as channels of distribution, among which the priority is given to modern mass media, have been identified. The main tasks and the importance of social advertising in the evolutionary development of society have been established. Social advertising is not only a marker of democratic and humanistic developments of the society, but also an important investment in the future, since it performs pedagogical and socio-corrective functions. The efficiency of social impact of advertising depends essentially on the target audience, its emotional, physical conditions, intellectual level, age, gender, experience, occupation, etc., and its effectiveness depends on the communication mechanisms of influence on the individual information goals and information needs of the society. Conclusions. The constitutive features, origin, tasks, and function of social advertising in the modern communication space are inspired by evolutionary changes in the dynamic, informational and technical society and are able to engage a broad segment of mass audience into the solution of global problems.